An Investigation Into The Interactive Role of Interest Rate Spread, Inflation, Foreign Direct Investment and Economic Growth in the Corporate Debt Financing: A Case Study of Pakistan - Sohail, Amjed; Muhammad, Imranullah; Adnan, Riaz (2018)
This study aims to investigate the dynamic relationship among the corporate financial policy, macroeconomic and institutional factors through error correction model in Pakistan over the period from 1975 to 2013. We used the cointegration methodology to study the long run short run effect of selected macroeconomic factors on the corporate borrowing patterns. The direction of causality is studied by Granger causality test within the framework of VECM. We note that inflation, foreign direct investment, and economic growth are significant determinants of long-run corporate financial policy. Interest rate spread has a negative short-run impact on the corporate borrowing. There is a long run capital structure equilibrium and any deviation from the long-run path is corrected at the rate of 23% annually if other things remain same. We also found that there is a reciprocal causal relation between corporate financial policy and economic growth. Corporate financial policy induces the FDI in the short run. The empirical results indicate that the corporate financial policy shares a stochastic linear trend with a country's macroeconomic and financial conditions. Keywords: Corporate financial policy, Economic growth, Fiscal policy, Adjustment speed